5000 years of lacustrine ecosystem changes from Lake Petit (Southern Alps, 2200 m a.s.l.): Regime shift and resilience of algal communities. (August 2015) - Cartier, Rosine; Brisset, Elodie; Paillès, Christine; Guiter, Frédéric; Sylvestre, Florence; Ruaudel, Florence; Anthony, Edward J; Miramont, Cécile
Sediments from Lake Petit (2200 m a.s.l., Southern Alps) are particularly relevant for analysis of coupled landscape palaeoecology and palaeolimnology. Diatom assemblages, organic matter composition of sediments (total nitrogen and organic carbon) and Pediastrum boryanum concentrations were obtained from a 144-cm-long core, enabling the reconstruction of the aquatic ecosystem over nearly the last 5000 cal. BP. From 4800 to 4300 cal. BP, Lake Petit was a stable diatom-productive water body dominated by alkaliphilous diatoms ( Staurosirella pinnata ). During this period, nutrients and cations were supplied by the chemical weathering of podzols that developed under conifer woodlands. This overall stability was suddenly interrupted at 4200 cal. BP by a major detrital pulse that was probably climate linked (4200 cal. BP event) and that triggered a drop in diatom productivity and diversity. From 4100 to 2400 cal. BP, diatom productivity progressively decreased, whereas Pediastrum developed. Diatom assemblages were more diversified (predominance of Pseudostaurosira robusta, P. brevistriata and P. pseudoconstruens ) and reflected a regime of continuous erosion, whereas slopes were colonised by grazed grasslands. Finally, from 2400 cal. BP to the present day, diatom assemblages reveal a slight acidification and nutrient enrichment of waters concomitant with increasing human pressure in the catchment. These results demonstrate the close links between ecosystems and the ready propagation of disturbances throughout watersheds that might lead to abrupt regime shifts in such alpine environments.